Moving people to deliver services - Mattoo, Aaditya; Carzaniga, Antonia (Washington, DC : World Bank, Oxford University Press, 2003)
The book brings together contributions from service providers, regulators (including ministries of labor and justice), researchers, trade negotiators, and the private sector. They provide a broad range of perspectives on the one central question: How can service trade liberalization be accomplished in a way that benefits both home and host countries? The result is a balanced consideration of the issues surrounding WTO labor mobility negotiations at a historically critical juncture.
Includes bibliographical references and index.
oif 31/08/15
Loan
Keywords: International trade; Service industries; Free trade; Emigration and immigration